PENGARUH KARAKTERISTIK BIOGRAFI TERHADAP CAKUPAN UKGS III OLEH PERAWAT GIGI DI KABUPATEN SEMARANG - Bambang Sutomo; Prasko ,; Bedjo Santoso (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2014)
TITLEInfluence of biography characteristic to UKGS III coverage by dental nurse in Semarang DistrictABSTRACTIn order to realize the development of health, one of which strived through the improvement of health care facilities. Health care facilities that are directly related to the community health center. Of its services by the health center, including prevention services via UKGS. UKGS coverage is still low, with the average number of new coaching first time visit to the elementary school in one year. This situation is still below the target of 2 times per year. Coverage SD UKGS fostered selective (stage III) reached 19.7%, still below the target of 30% of the elementary schools should be doing UKGS selective (stage III). The purpose of the study to know the effect of the characteristics of a biography of UKGS III coverage by the dental nurse inSemarangdistrict.Research carried out by the non-experimental design, the category of the type of quantitative research is descriptive and explanatory study. Subjects were the entire dental nurses working in health centers inSemarangdistrict as many as 35 people. Data analysis will be performed using univariate, bivariate and multivariate analyzes. Bivariate analysis done by correlation testChi Squarewith a 95% confidence level (α = 0.05). Ha accepted if the p value 0.05. Test the effect by using multiple logistic regression multivariate analysis with α = 0.05.The results of research on the scope UKGS III dental nurse in coaching UKBM, UKGS coverage either category III (51.4%), older age group of 19 people (54.3%), educational background dental nurse was found with SPRG categories (26, 7%). state of the working period at most dental nurse working group long term (14-28 years) of 54.3%. Results of correlation tests performed withChi Squarethere is one variable that is related: education p value = 0.005, and there are two variables that showed no association namely: age variable p value = 0.060. The test results showed the effect was no significant effect of the level of education of respondents to the coverage UKGS III in Semarang district by using multivariate logistic regression analysis obtained p value with OR = 0.017 (Exp B) = 15.11. In addition to the OR obtained (Exp B) = 15.11 can be interpreted that if there is a dental nurse who has a higher education tend to be achieved coverage UKGS III with both categories 15 times, rather than dental nurses in secondary education (SPRG). Advice to the Head of Puskesmas Semarang District Health Office to provide opportunities for dental nurses undertake further education. Dental nurse to increase the activity UKGS improve coverage and further improve the frequency of coaching. Key words : biography characteristics, scope of Stage III UKGS